Time Pattern of Male-Female Wage Differentials : Ontario 1946-71 - Gunderson, Morley (Relations industrielles / Industrial Relations, 1976)
In this paper the author examines whether male-female wage differentials have narrowed over time, whether such differentials narrow or widen at the peak of a business cycle, and whether the stricter enforcement of equal pay legislation in recent years has influenced these differentials.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Case for Government Supported Training Program - Gunderson, Morley (Relations industrielles / Industrial Relations, 1974)
Concepts of Public Expenditure Economies are applied to the operation of labour markets in general and training programs in particular to see if the free market provides a socially optimal amount of training. The case for government-supported training is discussed when there exist market imperfections and equity considerations, as well as market failure due to externalitiesyhigh risk and uncertainty, and merit goods.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z